A dynamic gradient ratio test apparatus - Khan, M.W.; Dawson, A.R.; Marshall, A.M. (Elsevier, 2018)
The soil-geotextile filtration mechanism is a complex process which depends on physical compatibility between the geotextile and the soil to be retained. Several methods have been proposed by researchers for assessing the filtration behaviour of soil-geotextile composite systems under steady state conditions. The Gradient Ratio (GR) test is the most commonly used method for measuring filtration compatibility of soil-geotextile systems. This paper describes the design of a modified GR permeability test apparatus to overcome disadvantages associated with traditional GR test devices. The apparatus can perform filtration tests under static and dynamic conditions and can be used to evaluate the filtration compatibility of fine-grained soils with geotextiles. The apparatus is incorporated within a triaxial testing system, hence representative field stress conditions can be applied to test specimens. Some exemplar GR tests performed on coarse and fine-grained soils with a non-woven geotextile are presented in this paper. Unidirectional dynamic loads are applied within the filtration tests to replicate highway traffic loading. Test results show that dynamic loading affects the filtration behaviour at the soil-geotextile interface by increasing the fine particles migration towards the geotextile, but that, for the soil evaluated here, this effect was small.